Up-regulation of hypoxia-inducible factor 1 alpha and hemodynamic responses following massive small bowel resection, - Rowland, Kathryn J. (2013)
PURPOSE: Massive small bowel resection (SBR) results in an adaptive response within the remnant bowel. We have previously shown an immediate reduction in intestinal blood flow and oxygen saturation (sO(2)) after SBR. We therefore sought to determine the duration of resection-induced intestinal hypoxia and expression of hypoxia-inducible factors (HIFs) following SBR. METHODS: C57B6 mice were subjected to 50% proximal SBR or a sham procedure. Photoacoustic microscopy (PAM) was used to measure blood flow and sO(2) on postoperative days (PODs) 1, 3, and 7. Ileal tissue was harvested 6 h postoperatively and on PODs 1 and 2, and HIF1α, HIF2α, and VEGF mRNA expression were assessed via RT-PCR. A p value of less than 0.05 was considered significant. RESULTS: Following SBR, reduction in intestinal blood flow persists for 24 h and is followed with hyperemia by POD 3. The immediate reduction in venous sO(2) and increased tissue oxygen utilization continued through POD 7. Enhanced expression of HIF1α was demonstrated 6 h following SBR. CONCLUSION: Massive SBR results in an immediate relative hypoxic state within the remnant bowel with early enhanced expression of HIF1α. On POD 7, increased tissue oxygen extraction and elevated blood flow persist in the adapting intestine.